Exploring the anatomical and metabolomic variabilities in the seagrass Posidonia oceanica (L.) Delile fruits - Federico Pinna; Mauro Commisso; Flavia Guzzo; Simonetta Bagella; Giulia Ceccherelli; Giovanna Becca; Maria Franca Usai; Patrizia Stipcich (Marine Biology, 2026)
Anatomical and metabolomic variability in marine plants can provide valuable insights into species adaptive strategies and resilience to environmental changes. This study explores the anatomical characteristics and metabolomic profiles of Posidonia oceanica fruits, a key Mediterranean seagrass species, collected from three areas in Sardinia (Alghero, Oristano, and Olbia). Anatomical analyses of pericarps assessed cuticle thickness and intercellular spaces. Additionally, metabolomic analyses were performed using UPLC-HRMS on both the pericarps and the seeds. Significant differences in the percentage of intercellular spaces among pericarps from the different areas were found, with those from Alghero, exhibiting a higher percentage. Metabolomic analyses highlighted distinct profiles across areas, with Alghero pericarps showing greater metabolomics complexity, characterized by high levels of chicoric acid, hydroxycinnamate and hydroxybenzoate derivatives, while seeds exhibited an abundance of procyanidins, benzoic and caffeic acids and quercetins. Interestingly, seeds from Olbia presented a higher abundance of lipids. This study provides the first comprehensive metabolomic characterization of P. oceanica pericarps and seeds, highlighting significant variability that may influence seed dispersal, germination, and species adaptability. Our findings offer new perspectives for the conservation and management of this key species, which are particularly relevant in the context of global climate change.

The role of cytokinin receptors in Arabidopsis thaliana seed development and how they affect the metabolomic profile - Domenico Loperfido; Cecilia Zumajo-Cardona; Mauro Commisso; Flavia Guzzo; Barbara Ambrose; Lucia Colombo; Ignacio Ezquer (Planta, 2025)

Nitrate induction and physiological responses of two maize lines differing in nitrogen use efficiency: effects on N availability, microbial diversity and enzyme activity in the rhizosphere - Zeno Varanini; Stefano Cesco; Nicola Tomasi; Roberto Pinton; Flavia Guzzo; Anita Zamboni; Brigitte Schloter-Hai; Michael Schloter; Laura Giagnoni; Mariarita Arenella; Paolo Nannipieri; Giancarlo Renella (Plant and Soil, 2018)

Metabolomic analysis reveals that the accumulation of specific secondary metabolites in Echinacea angustifolia cells cultured in vitro can be controlled by light - Chiara Francesca Guarnerio; Marica Fraccaroli; Irene Gonzo; Giovanna Pressi; Roberto Dal Toso; Flavia Guzzo; Marisa Levi (Plant Cell Reports, 2012)

Pre-analytical method for metabolic profiling of plant cell cultures of Passiflora garckei - Marica Fraccaroli; Silvia Nicoletti; Federica Maltese; Young Hae Choi; Flavia Guzzo; Marisa Levi; Robert Verpoorte (Biotechnology Letters, 2008)

Magnetic sorting in plant tissue: immunoseparation of pea nuclei with an antibody against nucleoporin - Paola Malacrino; Stefania Grignani; Flavia Guzzo; Marisa Levi (Biotechnology Letters, 1998)

The secretory nature of the lesion of carrot cell variant ts11, rescuable by endochitinase - Barbara Baldan; Flavia Guzzo; Francesco Filippini; Marine Gasparian; Fiorella LoSchiavo; Alessandro Vitale; Sacco C. de Vries; Paola Mariani; Mario Terzi (Planta, 1997)